2012
DOI: 10.3892/or.2012.2047
|View full text |Cite
|
Sign up to set email alerts
|

LOH 19q indicates shorter disease progression-free interval in low-grade oligodendrogliomas with EMP3 methylation

Abstract: Abstract. We previously described a cohort of grade II oligodendroglioma (OII) patients, in whom the loss of heterozygosity (LOH) 19q was present in the subgroup at a higher risk of relapse. In this study, we evaluated the CpG methylation of the putative tumor suppressor epithelial membrane protein 3 (EMP3, 19q13.3) gene promoter in the same OII cohort, to investigate whether a correlation could be found between EMP3 cytogenetic and epigenetic loss and higher risk of relapse. Twenty-three tumor samples from OI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
2
7
0
Order By: Relevance
“…It is more frequent in WHO grade II tumors (71.4%) than in WHO grade III tumors (44.7%), in agreement with previous observations [7, 16]. EMP3 promoter hypermethylation is prevalent in oligodendroglial tumors (63%) and in oligoastrocytomas (70%) upon astrocytic tumors (18%), as already reported [5, 7, 8, 13, 14, 16, 17]. Among GBMs, its prevalence in secondary tumors is confirmed [7, 16].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is more frequent in WHO grade II tumors (71.4%) than in WHO grade III tumors (44.7%), in agreement with previous observations [7, 16]. EMP3 promoter hypermethylation is prevalent in oligodendroglial tumors (63%) and in oligoastrocytomas (70%) upon astrocytic tumors (18%), as already reported [5, 7, 8, 13, 14, 16, 17]. Among GBMs, its prevalence in secondary tumors is confirmed [7, 16].…”
Section: Discussionsupporting
confidence: 91%
“…EMP3 is hypermethylated in 17% of primary GBMs (pGBMs) and in 89% of secondary GBMs (sGBMs), respectively [7]. These observations have been confirmed by other studies [817]. Normal nervous tissue showed neither EMP3 hypermethylation nor lack of mRNA expression [10].…”
Section: Introductionsupporting
confidence: 54%
“…EMP3 was one of the hub genes in this network. Previous results suggested that EMP3 was a critical biomarker in glioma prognosis [28][29][30][31][32]. EMP was connected with TIMP1 and SERPINE1 and SERPINE1 was connected with IGFBP2 ( Figure 3D).…”
Section: Validation Of Age Related Genes In Glioma Patients Derived Fmentioning
confidence: 65%
“…The prognostic effects of EMP3 [28][29][30][31][32] and IGFBP2 [33][34][35] in glioma patients are extensively studied. Here, we find two EMP3 and IGFBP2 associated genes TIMP1 and SERPINE1 are also suitable biomarkers for prognosis of glioma patients.…”
Section: Discussionmentioning
confidence: 99%
“…EMP3 is a member of the PMP22/EMP/MP20 gene family that plays a role in cell proliferation and cell-cell interactions [27]. Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30]. Moreover, EMP3 promoter hypermethylation is associated with a favorable prognostic significance in OS in patients with oligodendroglial and glioblastoma [29, 31, 32].…”
Section: Discussionmentioning
confidence: 99%